The sensitive to freezing3 mutation of Arabidopsis thaliana is a cold-sensitive allele of homomeric acetyl-CoA carboxylase that results in cold-induced cuticle deficiencies - Amid, Azura; Lytovchenko, Anna; Fernie, Alisdair R.; Warren, Garreth J.; Thorlby, Glenn J. (Oxford University Press, 2012)
The sfr3 mutation causes freezing sensitivity in Arabidopsis thaliana.Mapping, sequencing, and trangenic complementation showed sfr3 to be a missense in ACC1, an essential gene encoding homomeric (multifunctional) acetyl-CoA carboxylase. Cuticle permeability was compromised in the sfr3 mutant when plants were grown in the cold but not in the warm.Wax deposition on the inflorescence stem of cold-grown sfr3 plants was inhibited and the long-chain components of their leaf cuticular wax were reduced compared with wild-type plants. Thus, freezing sensitivity of sfr3 appears, from these results, to be due to cuticular deficiencies that develop during cold acclimation. These observations demonstrated the essential role of the cuticle in tolerance to freezing and drought.